2009
DOI: 10.1515/jpem.2009.22.10.895
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Levels of the Soluble Receptor (sRAGE) for Advanced Glycation Endproducts (AGEs) and their Receptor (RAGE) in Peripheral Blood Mononuclear Cells of Children with Type 1 Diabetes Mellitus

Abstract: Aim-, The binding of AGEs to RAGE is involved in diabetic vascular complications. We studied sRAGE levels and RAGE protein expression (P) together with N-carboxymethyl lysine (CML), a major AGE, in 74 patients with type 1 diabetes mellitus (DM1) and 43 healthy (C) children. Methods: sRAGE and CML levels were determined by ELISA and RAGE P was evaluated in mononuclcar cells by Western immunoblotting.Results: Serum sRAGE was higher in DM1 than in C (1430 ± 759 vs 1158 ± 595 pg/ml, ρ = 0.047), inversely correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…A few researchers have detected serum AGEs concentrations in children and adolescents with T1DM [28][29][30]37]. Some authors suggest that the measurement of serum AGEs concentrations may be useful in predicting the risk of diabetic complication development [30,37]. In our studies, the ROC analysis showed that it is not the serum AGEs level, but TNFa, diabetes duration and VEGF 165 were better factors in predicting the occurrence of microangiopathy in children and adolescents with T1DM.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A few researchers have detected serum AGEs concentrations in children and adolescents with T1DM [28][29][30]37]. Some authors suggest that the measurement of serum AGEs concentrations may be useful in predicting the risk of diabetic complication development [30,37]. In our studies, the ROC analysis showed that it is not the serum AGEs level, but TNFa, diabetes duration and VEGF 165 were better factors in predicting the occurrence of microangiopathy in children and adolescents with T1DM.…”
Section: Discussionmentioning
confidence: 49%
“…The threshold value for serum AGEs concentrations was established at the level of 19867 pg/ml. A few researchers have detected serum AGEs concentrations in children and adolescents with T1DM [28][29][30]37]. Some authors suggest that the measurement of serum AGEs concentrations may be useful in predicting the risk of diabetic complication development [30,37].…”
Section: Discussionmentioning
confidence: 99%
“…There are not many reports comparing sRAGE concentrations between children and adolescents with type 1 diabetes and healthy controls. Dettoraki et al (31) reported higher concentrations in the diabetic patients, whereas Giannini et al (32) observed the opposite. The groups were not matched for the HLA genotype in those studies, and the investigators in the latter study reported differences in the kidney function between the cases and the controls (31), which could influence the results.…”
Section: Discussionmentioning
confidence: 94%
“…AGEs derived from arginine are the following: glyoxal-derived hydroimidazolone (G-H1), methilglyoxal derived hydroimidazolone (MG-H1) and 3-deoxyglucosone derived hydroimidazolone (3DG-H1). Other AGEs such as 1-alkyl-2-formyl-3, 4-glycosyl pyrrole (AFGP), 2-(2-fluoril)-4, 5-furanyl-imidazole-1(FPI) and pentosidine are fluorescent (15,48) . Figure 3 illustrates the phases of Maillard reaction with the formation of three different AGEs.…”
Section: Agesmentioning
confidence: 99%
“…Other investigations still suggest that sRAGE concentrations may be high in response to circulating AGEs, hence becoming a reliable vascular injury marker in patients with DM2 (51) . Additionally, it has been reported that an increase in sRAGe in children with DM1 may protect cells temporarily against injuries caused by AGEs and it may be sufficient to eliminate the excess of circulating CML (15) . Yet another research reported the inverse association between esRAGE concentrations and renal alterations in children with DM1, implying the importance of this isoform in early stages of diabetic nephropathy (20) .…”
Section: Hoursmentioning
confidence: 99%